2012
DOI: 10.1371/journal.pone.0045873
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Organic Solvents Induce Renal Injury in Rats

Abstract: To investigate the injury effects of organic solvents on kidney, an animal model of Sprague-Dawley (SD) rats treated with mixed organic solvents via inhalation was generated and characterized. The mixed organic solvents consisted of gasoline, dimethylbenzene and formaldehyde (GDF) in the ratio of 2∶2:1, and were used at 12,000 PPM to treat the rats twice a day, each for 3 hours. Proteinuria appeared in the rats after exposure for 5–6 weeks. The incidences of proteinuria in male and female rats after exposure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…Whereas, serum creatinine (0.698±0.025 mg/dl) was within the normal ranges and had no significant differences with those of controls (0.657±0.024 mg/dl), this results are accepted with previous study (Abou-ElWafa, et al, 2015). Most of chemical substances are toxic to many organ systems including the kidney (W. Qin, et al, 2012), which may be attributed to an increase in liberating toxic metabolites including reactive oxygen species. While experiments with rats indicate that exposure by inhalation to the aromatic hydrocarbons toluene, styrene, and xylene was nephrotoxic (Rankin, et al, 2008), this effect has not been confirmed in man (Melnick, 1992).…”
Section: Resultssupporting
confidence: 77%
“…Whereas, serum creatinine (0.698±0.025 mg/dl) was within the normal ranges and had no significant differences with those of controls (0.657±0.024 mg/dl), this results are accepted with previous study (Abou-ElWafa, et al, 2015). Most of chemical substances are toxic to many organ systems including the kidney (W. Qin, et al, 2012), which may be attributed to an increase in liberating toxic metabolites including reactive oxygen species. While experiments with rats indicate that exposure by inhalation to the aromatic hydrocarbons toluene, styrene, and xylene was nephrotoxic (Rankin, et al, 2008), this effect has not been confirmed in man (Melnick, 1992).…”
Section: Resultssupporting
confidence: 77%
“…The intermediate filament protein (desmin) had been known as an indicator of podocytic injury. The expression was often upregulated in various glomerular diseases in which podo cytic injuries were involved [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Fuel products are mixtures of aliphatic and aromatic hydrocarbons mostly related to gasoline; most of them are toxic to many organ systems including the kidney [ 24 , 25 ], which may be attributed to an increase in liberating toxic metabolites including reactive oxygen species. While experiments with rats indicate that exposure by inhalation to the aromatic hydrocarbons toluene, styrene, and xylene was nephrotoxic [ 26 ], this effect has not been confirmed in man [ 27 ].…”
Section: Discussionmentioning
confidence: 99%